THE QUALITATIVE EVIDENCES THAT DIFFERENTIATE PELAGA AND TAMBAKAN DIALECTS: A CONTRASTIVE STUDY - Mahardika, P. B.; Budasi, I. G.; Marjohan, A. (Jurnal Pendidikan Bahasa Inggris undiksha, 2018)
AbstractThe study aimed at contrasting the phonological systems of Pelaga Dialect (PD) and Tambakan Dialect (TD) and its implication to learning English as a foreign language. The subjects of this study were Pelaga and Tambakan dialects. This study was a contrastive research. The phonological systems of both dialects were firstly described. The obtained data in the form of wordlists (Swadesh, Budasi, and Holle) were collected through recording and listening and noting techniques. The result of the study shows that PD and TD have differences. In terms of phonemes, it was found that PD had 55 phonemes and TD had 48 phonemes. In term of vowel, the distribution of the vowels is different, although they have the same number of it. PD has 9 diphthongs and TD also has 9 diphthongs. From the 19 consonants of both dialects, most of the consonant have complete distribution. There is only the distribution of consonant /ʔ/ that differentiates both dialects in which in PD consonant /ʔ/ appears in the middle and final position, while in TD it appears in the final position only. In term of consonant cluster, PD has 17 consonant clusters and TD only has 11 consonant clusters. On the implication to learning English as a foreign language, English phonemes /ӕ/, /ɒ/, /ɜ/, /ɑ/, /ɑI/, /ɑʊ/, /f/, /v/, /ɵ/, /ð/, /z/, /ʃ/, /ʤ/ and all of the English triphthong are difficult to be pronounced by people in Pelaga and Tambakan. Keywords : qualitative evidences, Pelaga dialect,  Tambakan dialect, contrastive study